Positive electrode active material for secondary battery, its manufacturing method, free-standing film containing the same, dry positive electrode, and secondary battery containing dry positive electrode
By coating lithium transition metal oxide with an amorphous carbon-based and carbon nanotube layer, the electrode active material addresses solvent evaporation issues and PTFE fiberization challenges, improving battery conductive paths and performance.
Patent Information
- Application Number
- JP2023526442
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-24
- Filing Date
- 2021-11-26
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2041-11-26
AI Technical Summary
The manufacturing of lithium secondary batteries is hindered by solvent evaporation issues that lead to defects like pinholes and cracks in the electrode active layer, resulting in non-uniform drying and poor electrode quality, especially for thick film electrodes, and the use of polytetrafluoroethylene (PTFE) as a binder faces challenges in fiberization due to smooth surfaces and shearing forces.
A positive electrode active material is developed with a lithium transition metal oxide coated by an amorphous carbon-based layer and a carbon nanotube layer, formed through a mechanofusion method, enhancing conductive paths and improving PTFE binder fiberization.
This approach improves the conductive path between active materials, reduces battery resistance, and enhances electrode productivity and durability by ensuring proper fiberization of PTFE, leading to better lifespan and output characteristics in secondary batteries.
Smart Images

Figure 0007608010000003 
Figure 0007608010000004 
Figure 0007608010000001
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0164640 filed on November 30, 2020 and Korean Patent Application No. 10-2021-0163398 filed on November 24, 2021, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a positive electrode active material for a secondary battery, a method for producing the same, a free-standing film containing the same, a dry positive electrode, and a secondary battery containing the dry positive electrode. [Background technology]
[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is the field of power generation and storage using electrochemistry.
[0004] At present, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and the range of its use is tending to expand more and more.
[0005] Lithium secondary batteries, which are representative of such secondary batteries, are not only used as an energy source for mobile devices, but are also being used as a power source for electric vehicles and hybrid electric vehicles to replace vehicles that use fossil fuels such as gasoline vehicles and diesel vehicles, which are one of the main causes of air pollution, and their range of use is expanding as an auxiliary power source for grid-connected vehicles.
[0006] The manufacturing process of such lithium secondary batteries is roughly divided into three stages: electrode process, assembly process, and chemical formation process. The electrode process is further divided into active material mixing process, electrode coating process, drying process, rolling process, slitting process, winding process, etc.
[0007] Among these, the active material mixing process is a process of blending a coating material for forming an electrode active layer where an actual electrochemical reaction occurs in the electrode. In detail, the electrode active material, which is an essential element of the electrode, and other additives such as a conductive material and a filler, a binder for binding between particles and adhering to the current collector, and a solvent for imparting viscosity and dispersing particles are mixed to prepare a slurry having fluidity.
[0008] The composition mixed to form the electrode active layer is also called an electrode mixture in a broad sense.
[0009] Thereafter, an electrode coating process is performed in which the electrode mixture is applied onto an electrically conductive current collector, and a drying process is performed in which the solvent contained in the electrode mixture is removed. The electrode is then rolled to a predetermined thickness.
[0010] Meanwhile, the evaporation of the solvent contained in the electrode mixture during the drying process may induce defects such as pinholes and cracks in the already formed electrode active layer. In addition, since the inside and outside of the active layer are not dried uniformly, particle floating phenomenon due to the difference in evaporation speed of the solvent, that is, particles in the area that is dried first float up and form gaps with the area that is dried later, which may deteriorate the quality of the electrode. Therefore, there is a fatal drawback that it is difficult to manufacture thick film electrodes.
[0011] In order to solve the above problems, drying devices capable of adjusting the evaporation rate of the solvent while uniformly drying the inside and outside of the active layer have been considered. However, such drying devices are very expensive and require considerable cost and time for operation, which is disadvantageous in terms of manufacturing process.
[0012] Therefore, recently, active research has been conducted into the production of dry electrodes without using solvents.
[0013] The dry electrode is generally manufactured by laminating a free-standing film, which includes an active material, a binder, a conductive material, etc., on a current collector.
[0014] Therefore, it is attracting attention as an innovative technology that makes it possible to manufacture thick-film electrodes, does not require the use of organic solvents that are harmful to the human body, and simultaneously solves issues such as high process costs due to long drying times.
[0015] In addition, when manufacturing such dry electrodes, polytetrafluoroethylene (PTFE) powder is mainly used as a binder. Such PTFE has long fibers tightly stacked inside the particles, and when it receives shear force under certain conditions, it breaks out as long fibers. These fibers connect active materials with each other and active materials with conductive materials to maintain the shape of the electrode.
[0016] However, on the smooth surface of the positive electrode material, PTFE is not rubbed well and is not easily subjected to shear force, so fiberization is unlikely to occur. Furthermore, if PTFE fiberization does not occur, not only is it difficult to maintain the electrode shape, but it also has a negative effect on electrode productivity and cell durability, so PTFE fiberization is very important.
[0017] Therefore, there is a pressing need to develop a dry electrode technology that can solve these problems. Summary of the Invention [Problem to be solved by the invention]
[0018] The present invention is intended to solve the above problems, and aims to provide a positive electrode active material that not only easily induces PTFE binder fiberization but also improves the conductive path between active materials to reduce battery resistance, and a method for producing the same.
[0019] Another object of the present invention is to provide a dry electrode containing such a positive electrode active material, and as a result, to provide a secondary battery that contains such a dry electrode and can have improved life and output characteristics. [Means for solving the problem]
[0020] A positive electrode active material for a secondary battery according to one embodiment of the present invention, Lithium transition metal oxide particles; an amorphous carbon-based coating layer formed in the form of a coating on the surface of the lithium transition metal oxide particles; and A positive electrode active material is provided, which includes a carbon nanotube coating layer formed on the amorphous carbon-based coating layer.
[0021] In one specific example, the amorphous carbon-based coating layer may be physically bound to the lithium transition metal oxide particles in the form of a coating.
[0022] The amorphous carbon-based coating layer may contain carbon black.
[0023] In one specific example, the carbon nanotube coating layer may have a pi-pi interaction with the amorphous carbon-based coating layer.
[0024] In one specific example, the amorphous carbon-based material of the amorphous carbon-based coating layer and the carbon nanotubes of the carbon nanotube coating layer may each be included in an amount of 0.01 to 5 wt % of the total weight of the active material.
[0025] The positive electrode active material may have a convexity of 0.6 to 0.9.
[0026] Meanwhile, a method for preparing a positive electrode active material for a secondary battery according to another embodiment of the present invention includes: (a) coating the surface of a lithium transition metal oxide particle with an amorphous carbon-based material in the form of a coating; and (b) secondarily coating the surfaces of the primarily coated particles with carbon nanotubes to produce a positive electrode active material.
[0027] In one specific example, in step (a), the amorphous carbon-based material has a hollow structure, and the structure collapses during coating, so that the amorphous carbon-based material can be physically bound to the surface of the lithium transition metal oxide in the form of a coating.
[0028] Moreover, the coating in steps (a) and (b) can be carried out by a mechanofusion method.
[0029] In addition, in one specific example, in step (b), the carbon of the carbon nanotube may form π-π interactions with the carbon of the amorphous carbon-based material.
[0030] In one specific example, the amorphous carbon-based material and the carbon nanotubes may be coated in steps (a) and (b) so as to be contained in an amount of 0.01 to 5 wt % of the total weight of the active material, respectively.
[0031] Meanwhile, according to another embodiment of the present invention, there is provided a free-standing film including the positive electrode active material and a binder, the binder including polytetrafluoroethylene (PTFE).
[0032] In one specific example, the polytetrafluoroethylene may be in the form of fibers surrounding the active material.
[0033] In one specific example, the free-standing film may further include a conductive material.
[0034] In one specific example, the room temperature tensile strength of the dry positive electrode is 0.15 to 1 kgf / mm 2 It could be.
[0035] The present invention also provides a dry positive electrode in which the free-standing film is formed on a positive electrode current collector, and a secondary battery including the dry positive electrode. [Brief description of the drawings]
[0036] [Figure 1] 4 is a SEM photograph showing that the amorphous carbon-based coating layer according to Preparation Example 1 is formed in the form of a coating film. [Diagram 2] 1 is a SEM photograph showing that the amorphous carbon-based coating layer according to Comparative Production Example 1 is formed in a particulate form. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] The present invention will now be described in more detail to provide a better understanding of the present invention.
[0038] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that is appropriate to the technical idea of the present invention, based on the principle that the inventor himself can appropriately define the concept of the term in order to explain the invention in the best possible way.
[0039] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless a different meaning is clearly indicated in the context.
[0040] Also, throughout the specification, when a part "comprises" a certain element, this means that it may further include other elements, but not excluding other elements, unless specifically stated to the contrary.
[0041] According to one embodiment of the present invention, there is provided a positive electrode active material for a secondary battery, comprising: Lithium transition metal oxide particles; an amorphous carbon-based coating layer formed in the form of a coating on the surface of the lithium transition metal oxide particles; and A positive electrode active material is provided, which includes a carbon nanotube coating layer formed on the amorphous carbon-based coating layer.
[0042] Here, the lithium transition metal oxide particles of the positive electrode active material include all conventionally known lithium transition metal oxides containing lithium, transition metals, and oxygen, such as layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) and compounds substituted with one or more transition metals; 1+x Mn 2-x Lithium manganese oxides such as LiMnO4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M x Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3); 2-x M x This concept includes all of the lithium manganese composite oxides represented by Li2Mn3MO8 (where M is Co, Ni, Fe, Cr, Zn, or Ta, and x is 0.01 to 0.1) or Li2Mn3MO8 (where M is Fe, Co, Ni, Cu, or Zn); and not only LiMn2O4, in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion, but also lithium metal phosphate LiMPO4 (where M is Fe, CO, Ni, or Mn), which is a phosphate form.
[0043] However, the lithium transition metal oxide particles generally used as the active material generally have a smooth surface. Therefore, when polytetrafluoroethylene (PTFE) is used as a binder for manufacturing a dry positive electrode, the lithium transition metal oxide particles and PTFE are not rubbed well and are not easily subjected to shear force, so that there is a problem that fiberization is not easily caused even by the high shear mixing.
[0044] Therefore, the inventors of the present application have repeatedly conducted in-depth research and have found that by coating the lithium transition metal oxide particles with a carbon-based material, a dual effect can be obtained in which the conductive path is improved while the unevenness of the particle surface is significantly improved, resulting in fiberization of PTFE through high shear mixing.
[0045] However, among the carbon-based materials, amorphous carbon-based materials partially improve the fiberization of PTFE due to the improved conductivity of lithium transition metal oxide and increased surface roughness, but since they are in particulate form, they lack conductive paths between active materials. When carbon nanotubes are directly coated on the surface of lithium transition metal oxide, the coating is not performed well because the carbon nanotubes are in tube form, and lumps form on the boundary surface of the primary particles, resulting in poor utilization relative to the amount added.
[0046] In addition, if the above materials were added together to solve this problem, the carbon would not be coated with the lithium transition metal oxide due to their good affinity with each other, and there would be a high probability that the amorphous carbon material and the carbon nanotubes would clump together.
[0047] Therefore, the inventors of the present application have found that by first coating the surface of a lithium transition metal oxide with a particulate, smoothly coated amorphous carbon-based material and then coating the carbon nanotubes, the above problems can be solved, and the carbon of the amorphous carbon-based material and the carbon of the carbon nanotubes have π-π interaction with each other, so that the carbon nanotubes do not fall off much and are smoothly coated, improving the conductive path between the active materials, reducing the battery resistance and improving the life and output characteristics. In addition, the degree of unevenness of the active material particle surface is significantly improved, resulting in a dual effect of causing PTFE to become fibrous due to friction during high shear mixing. This has led to the completion of the present invention.
[0048] Therefore, the order of the coating is very important, and if the coating layers are mixed together or the coating layers are formed in reverse, the intended effect of the present application cannot be obtained.
[0049] Specifically, the amorphous carbon-based coating layer is not limited to amorphous carbon and may include various substances, specifically, soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc., among which carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, etc., in particular, carbon black, and more specifically, the amorphous carbon-based coating layer may be a carbon black coating layer.
[0050] In this case, the amorphous carbon-based coating layer is not coated in the form of particles, but is physically bound to the lithium transition metal oxide particles in the form of a coating.
[0051] Specifically, when the carbon nanotubes are coated in particulate form, there is a high probability that they will later detach from the surface of the lithium transition metal oxide due to the lack of strong π-π interactions between the carbon nanotubes and the carbon nanotubes. Therefore, by firmly and physically bonding to the surface of the lithium transition metal oxide in the form of a coating, it is possible to effectively prevent the carbon nanotubes from detaching from the active material later by high shear mixing, etc.
[0052] Therefore, the formation of the amorphous carbon-based coating layer is not limited as long as it can be formed in the form of a coating as described above, but for example, it is performed by a high shear force mechanofusion method to facilitate the manufacturing process and to increase the physical binding strength of the amorphous coating layer.
[0053] However, if the positive active material and amorphous carbon precursor are mixed and heat treated, a chemical reaction may occur, which may change the oxidation number of the positive electrode surface. If the positive active material and amorphous carbon are simply mixed, the coating cannot be properly formed, and the amorphous carbon particles will be present in agglomeration at the boundary surface of the primary particles of the active material. Therefore, it is most preferable to use the mechanofusion method, which is a physical coating that is subjected to high shear force of several thousand rpm in the narrow gap between a vessel and an impeller, as this can form a thin and uniform surface coating.
[0054] The carbon nanotube coating layer may be formed on a surface of the amorphous carbon-based coating layer after the amorphous carbon-based coating layer is formed.
[0055] At this time, the carbon nanotube coating is not limited, but is preferably coated by the mechanofusion method.
[0056] Meanwhile, in the amorphous carbon-based coating layer and the carbon nanotube coating layer, the amorphous carbon-based material and the carbon nanotubes may be contained in an amount of 0.01 to 5 wt %, specifically 0.05 to 3 wt %, of the total weight of the active material, respectively.
[0057] That is, the amorphous carbonaceous material may be contained in an amount of 0.01 to 5 wt %, specifically 0.05 to 3 wt %, of the total weight of the active material, and the carbon nanotubes may be contained in an amount of 0.01 to 5 wt %, specifically 0.05 to 3 wt %, of the total weight of the active material.
[0058] If the content of each substance is too low outside the above range, the coating layer is not formed properly, and the intended effects of improving the conductive path and causing PTFE fiberization cannot be obtained, which is undesirable. Conversely, if the content is too high, the content of the coating layer increases relatively, which is undesirable from the viewpoint of the energy density of the battery.
[0059] When the thickness falls within the above range, each of the coating layers may be formed to a thickness of specifically 100 nm to 2 μm, more specifically 300 nm to 1.5 μm.
[0060] Meanwhile, the convexity of the positive electrode active material having the double coating layer formed thereon may be 0.6 to 0.9, specifically 0.65 to 0.85, more specifically 0.7 to 0.85, and most specifically 0.75 to 0.8.
[0061] The degree of envelopment means the degree of smoothness of the surface and can be measured, for example, by Morphologi 4 equipment of Marven Co., Ltd. An envelopment degree of 1 means a perfect sphere, and the more uneven the surface, the closer to 0 the envelopment degree is.
[0062] If the degree of envelopment of the positive active material is too high outside the above range, it means that the particles are nearly perfectly spherical and smooth, and the PTFE is not rubbed well during mixing, making it difficult to obtain a shear effect. If the degree of envelopment is too low, the surface unevenness is too severe, causing the PTFE particles to be trapped in deep boundaries, which is undesirable.
[0063] According to another embodiment of the present invention, there is provided a method for producing a positive electrode active material for a secondary battery, comprising the steps of: (a) coating the surface of lithium transition metal oxide particles with an amorphous carbon-based material in a dry manner under high shear force; and (b) providing a second coating of the surfaces of the first-coated particles with carbon nanotubes to produce a positive electrode active material;
[0064] As mentioned above, the amorphous carbon-based material is preferably coated on the surface of the lithium transition metal oxide particles in the form of a non-particulate coating.
[0065] Therefore, the amorphous carbon-based material has a hollow structure that allows a coating layer to be easily formed in a coating form by a dry mechanofusion method, and the structure collapses during coating, allowing the material to be physically bound to the surface of the lithium transition metal oxide in the form of a coating.
[0066] Meanwhile, the carbon of the carbon nanotubes forms π-π interactions with the carbon of the amorphous carbon-based material by coating in the step (b), so that the carbon nanotubes are firmly bound and coated so as not to be detached.
[0067] At this time, the coating in the steps (a) and (b) is carried out by the mechanofusion method as explained above.
[0068] As described above, the amorphous carbonaceous material and the carbon nanotubes may be coated in steps (a) and (b) so as to be contained in an amount of 0.01 to 5 wt %, more specifically 0.05 to 3 wt %, of the total weight of the active material.
[0069] Meanwhile, according to yet another embodiment of the present invention, there is provided a freestanding film including the positive electrode active material and a binder, the binder including polytetrafluoroethylene (PTFE).
[0070] The freestanding films are similar in that a mixture containing an active material and a binder is generally prepared, but the mixture is not prepared in a solvent but in powder form.
[0071] Specifically, the freestanding film is first prepared by subjecting a mixture containing the positive electrode active material and a binder to high shear mixing to fiberize the PTFE in the binder so that the PTFE is bound to the active material in a fibrous form, and then rolling the mixture to form a freestanding film corresponding to the positive electrode mixture.
[0072] Such rolling is called "calendering." By such calendering, the mixture is made into a film shape having an average thickness of, for example, 1 μm to 300 μm.
[0073] At this time, the rolling is performed, for example, by rolls that face each other, and at this time, the roll temperature may be 30° C. to 100° C., and the roll rotation speed may be 1 rpm to 40 rpm.
[0074] The free-standing film thus produced does not contain a solvent, and is therefore easy to handle and can be processed into a desired shape for use in the manufacture of various types of positive electrodes. In addition, the drying process for removing the solvent can be omitted, which can improve the manufacturing process of the positive electrode and greatly reduce the process cost.
[0075] Meanwhile, the freestanding film may further include a conductive material. In this case, the PTFE binder surrounds not only the active material but also the conductive material in the form of fibers.
[0076] Therefore, the binder must contain PTFE as an essential component. Specifically, the PTFE may be contained in an amount of 50% by weight or more based on the total weight of the binder. Of course, the binder may additionally contain PEO (polyethylene oxide), PVDF (polyvinylidene fluoride), and PVDF-HFP (polyvinylidene fluoride-co-hexafluoropropylene). However, in detail, the binder may contain only PTFE.
[0077] The conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber and metal fiber; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. In particular, in order to uniformly mix the conductive material and improve conductivity, the conductive material may include one or more selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes, and more particularly, it may include activated carbon.
[0078] This is a form in which the surface of the positive electrode active material is physically coated, and when the positive electrode active material according to the present invention is used, even a small amount of conductive material provides sufficient conductivity, which is preferable from the viewpoint of the energy density of the battery.
[0079] The mixture ratio of the active material, binder, and conductive material may be 85-99% by weight:0.5-10% by weight:0-5% by weight, more specifically, 90-99% by weight:0.5-5% by weight:0.5-5% by weight.
[0080] If the binder content is too high outside the above range, the binder may be excessively fiberized in the subsequent high shear mixing process, which may result in poor processability. If the binder content is too low, the binder may not be sufficiently fiberized, which may result in a weakened physical strength of the electrode.
[0081] Also, if the content of the conductive material is too high outside the above range, the content of the active material is relatively reduced, resulting in a problem of a decrease in the energy density of the battery.
[0082] Meanwhile, in some cases, a filler, which is a component that suppresses the expansion of the electrode, may be added to the free-standing film. The filler is not particularly limited as long as it does not induce chemical changes in the battery and is a fibrous material, and examples of the filler include olefin polymers such as polyethylene and polypropylene; glass fiber, carbon fiber, and other fibrous materials.
[0083] As described above, when the cathode active material according to the present invention is included, the PTFE fiberization is successfully performed, the binding strength between the active materials is increased, and the free-standing film is successfully formed, so that the room temperature tensile strength of the free-standing film can be improved.
[0084] Specifically, the free-standing film has a room temperature tensile strength of 0.17 to 1 kgf / mm 2 Specifically, the resistance may be 0.17 to 0.95 kgf / mm 2 , more specifically 0.2 to 0.3 kgf / mm 2 , most specifically 0.2~0.25kgf / mm 2 It could be.
[0085] The room temperature tensile strength was measured by pulling the free-standing film in the MD direction at room temperature at a cross head speed of 50 mm / min using a universal testing machine UTM (manufacturer: Zwick, Germany, model name: Z2.5 TN) according to JIS C 6511, a standard for mechanical property evaluation in the copper foil industry, and measuring the load at the time of breakage of the test piece. The tensile strength was calculated as follows: Tensile strength (kgf / mm 2 ) = Load value (kgf) / thickness (mm) x width (mm)
[0086] If the room temperature tensile strength is too low outside the above range, there is a risk of breakage or defects during processing, and the durability of the battery is weakened, which is undesirable.
[0087] The free-standing film is then pressed onto a positive electrode current collector to produce a dry positive electrode.
[0088] Therefore, the present invention also provides a dry type positive electrode in which the free-standing film is formed on a positive electrode current collector.
[0089] The pressing, i.e., lamination, for manufacturing the dry positive electrode may also be performed by a lamination roll, and at this time, the lamination roll may be maintained at a temperature of 30°C to 200°C.
[0090] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and examples of the positive electrode current collector include stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The current collector may also have fine irregularities on its surface to increase the adhesive strength of the positive electrode active material, and may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0091] According to another embodiment of the present invention, there is provided a secondary battery including the dry cathode. Specifically, an electrode assembly including the dry cathode, a separator, and an anode is housed in a battery case together with an electrolyte. Other configurations of the secondary battery are well known in the art, and therefore will not be described here.
[0092] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, the present invention will be described in detail based on examples, comparative examples, and experimental examples in order to enable those skilled in the art to easily understand the present invention.
[0093] <Production Example 1> The LiMnO2 active material is mixed with hollow carbon black at 1.5% by weight based on the active material using a Hosokawa Micron Corporation NOB-130 device by mechanofusion to coat the LiMnO2 particles with the carbon black in the form of a film.
[0094] <Comparative Manufacturing Example 1> The LiMnO2 active material was simply mixed with hollow carbon black at 1.5 wt % based on the active material using a Waring Blender to coat the LiMnO2 particles with the particulate carbon black.
[0095] <Experimental Example 1> SEM photographs of the materials prepared in Preparation Example 1 and Comparative Preparation Example 1 are shown in FIG. 1 and FIG. 2 below.
[0096] 1 and 2, when hollow carbon black was used and mixed by mechanofusion as in Preparation Example 1, it was confirmed that the carbon black was coated in a thin and uniform film form over the entire surface, whereas in Comparative Preparation Example 1, it was confirmed that the carbon black was solidified in particulate form at the boundary surface between the primary particles due to simple mixing.
[0097] <Example 1> The LiMnO2 particles produced in Preparation Example 1 and 1.5 wt% of carbon nanotubes were mixed by mechanofusion using NOB-130 equipment manufactured by Hosokawa Micron Corporation to obtain a positive electrode active material having a structure in which carbon nanotubes are coated on a carbon black coating layer.
[0098] <Example 2> The LiMnO2 active material is mixed with hollow carbon black at 0.5% by weight based on the active material using a Hosokawa Micron Corporation NOB-130 device by mechanofusion to coat the LiMnO2 particles with the carbon black in the form of a film.
[0099] The carbon black-coated LiMnO2 particles and 0.5 wt% of carbon nanotubes were mixed by mechanofusion using a NOB-130 device made by Hosokawa Micron Corporation to obtain a positive electrode active material having a structure in which carbon nanotubes are coated on a carbon black coating layer.
[0100] <Comparative Example 1> A positive active material was obtained in the same manner as in Example 1, except that LiMnO2 powder without any coating layer was used as the positive active material.
[0101] <Comparative Example 2> The LiMnO2 active material was mixed with hollow carbon black at 3% by weight using a Hosokawa Micron Corporation NOB-130 device by mechanofusion to obtain a positive electrode active material in which the carbon black was coated on the LiMnO2 particles in the form of a film.
[0102] <Comparative Example 3> The carbon nanotubes were mixed with the LiMnO2 active material at 3% by weight based on the active material by mechanofusion using a NOB-130 device manufactured by Hosokawa Micron Corporation, to obtain a positive electrode active material in which the LiMnO2 particles were coated with CNTs.
[0103] Comparative Example 4: Carbon black coating after CNT coating The carbon nanotubes are mixed with the LiMnO2 active material at 1.5% by weight based on the active material using a Hosokawa Micron Corporation NOB-130 device by mechanofusion to coat the LiMnO2 particles with the carbon nanotubes in a film form.
[0104] The carbon nanotube-coated LiMnO2 particles and 1.5 wt% of hollow carbon black were mixed by mechanofusion using a NOB-130 device manufactured by Hosokawa Micron Corporation to obtain a positive electrode active material having a structure in which carbon black is coated on a carbon nanotube coating layer.
[0105] <Comparative Example 5> Application of simple mixing without the Mechanofusion method The LiMnO2 particles prepared in Comparative Preparation Example 1 and 1.5 wt % of carbon nanotubes were added and simply mixed to obtain a positive electrode active material.
[0106] <Experimental Example 2> The interdigitation degrees of the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 to 5 were measured using a Morphologi 4 device manufactured by Malvern. As a result, the positive electrode active material of Example 1 had an interdigitation degree of 0.76, the positive electrode active material of Example 2 had an interdigitation degree of 0.80, the positive electrode active material of Comparative Example 1 had an interdigitation degree of 0.95, the positive electrode active material of Comparative Example 2 had an interdigitation degree of 0.98, the positive electrode active material of Comparative Example 3 had an interdigitation degree of 0.91, the positive electrode active material of Comparative Example 4 had an interdigitation degree of 0.92, and the positive electrode active material of Comparative Example 5 had an interdigitation degree of 0.96.
[0107] From the above results, it can be seen that the envelopment degree is reduced to 0.9 or less when a coating layer is formed as in Examples 1 and 2. On the other hand, it can be seen that the envelopment degree is still 0.9 or more in the comparative example.
[0108] <Experimental Example 3> The positive electrode active materials prepared in Examples 1 to 2 and Comparative Examples 1 to 5 and polytetrafluoroethylene (PTFE) as a binder were added to a Thermo Scientific Rheomix 300TM extruder so that the content of the binder was 3 wt % based on the total mixture, and mixed at room temperature for about 5 minutes under a maximum torque of 180NN and 50 rpm.
[0109] The mixture was placed in a wrap calendar (roll diameter: 100 mm, roll temperature: 85° C., 10 rpm) to produce a free-standing film with a thickness of 250 μm and a porosity of 35 to 40%.
[0110] The room temperature tensile strength of the free-standing film was measured as follows, and the results are shown in Table 1 below.
[0111] The tensile strength was measured according to JIS C 6511, a standard for mechanical property evaluation in the copper foil industry, by pulling the freestanding film in the MD direction at a cross head speed of 50 mm / min using a universal testing machine UTM (manufacturer: Zwick, Germany, model name: Z2.5 TN), and measuring the load at the time of breakage of the test piece. The tensile strength was calculated as follows: Tensile strength (kgf / mm 2 ) = Load value (kgf) / thickness (mm) x width (mm)
[0112] [Table 1]
[0113] Referring to Table 1, it can be seen that the room temperature tensile strength was improved in the present invention. This means that PTFE fiberization was more successful. In the case of Comparative Example 5, the same content and order of coating were used, but when simple mixing was used instead of the mechanofusion method, an amorphous carbon-based coating layer was not formed in the form of a coating, and it can be seen that the effect of the present invention could not be achieved.
[0114] <Experimental Example 4> The free-standing film had a loading capacity of 4.8mAh / cm 2 The laminate was placed on one side of an aluminum foil (20 μm) as a current collector so that the thickness of the laminate was 100 μm, and laminated with a lamination roll maintained at 100° C. to prepare an electrode.
[0115] At this time, the target thickness was 200 μm and the target porosity was 28 to 30%, and the gap of the lamination roll was adjusted so that the target thickness was within the above range.
[0116] A coin-type half cell was fabricated using the electrode and a 200 μm-thick lithium metal as a counter electrode, and an electrolyte containing 1M LiPF6 in a solvent of EC (ethylene carbonate):EMC (ethyl methyl carbonate) = 2:8.
[0117] The prepared coin-type half cell was charged and discharged 200 times at a current condition of 0.1C rate in a voltage range of 3.0 to 4.30V, and then the discharge capacity retention rate of 100 times was calculated based on the single discharge capacity. The results are shown in Table 2 below.
[0118] In addition, the coin-type half cell was discharged once at a current rate of 2C, and the capacity ratio relative to the 0.1C discharge capacity was calculated. The results are shown in Table 2 below.
[0119] [Table 2]
[0120] Referring to Table 2, it can be seen that the method of the present invention can improve the life and output characteristics. In Comparative Example 1, no conductive material was used, in Comparative Example 2, the surface of the coated active material was smooth and PTFE fiberization was not performed well, in Comparative Examples 3 and 4, the surface was hardened due to insufficient active material coating, and in Comparative Example 5, the same amount and order of coating were used, but when simple mixing was performed without mechanofusion, an amorphous carbon-based coating layer was not formed in the form of a coating, and therefore it was confirmed that the effects of the present invention could not be achieved.
[0121] According to the present invention, a positive electrode active material in which an amorphous carbon-based coating layer in the form of a coating film is formed on the surface of a lithium transition metal oxide particle and a carbon nanotube coating layer is formed on the amorphous carbon-based coating layer has improved conductivity due to these coating layers, but also has increased surface unevenness. Therefore, when used in a dry positive electrode, it not only easily causes PTFE binder fiberization to increase electrode productivity and improve battery durability, but also improves the conductive path between active materials to reduce battery resistance, thereby improving the life and output characteristics of a secondary battery including the same.
Claims
1. A positive electrode active material for a secondary battery comprising a polytetrafluoroethylene (PTFE) binder, Lithium transition metal oxide particles, an amorphous carbon-based coating layer formed in the form of a coating on the surface of the lithium transition metal oxide particle; and A carbon nanotube coating layer is formed on the amorphous carbon coating layer, The positive electrode active material has a convexity of 0.6 to 0.
9.
2. The positive electrode active material according to claim 1 , wherein the amorphous carbon-based coating layer is physically bound to the lithium transition metal oxide particles in the form of a coating.
3. The positive electrode active material according to claim 1 , wherein the amorphous carbon-based coating layer contains carbon black.
4. The positive electrode active material according to claim 1 , wherein the carbon nanotube coating layer has a π-π interaction with the amorphous carbon-based coating layer.
5. 2. The positive electrode active material according to claim 1, wherein the amorphous carbon-based material of the amorphous carbon-based coating layer and the carbon nanotubes of the carbon nanotube coating layer are each contained in an amount of 0.01 to 5 wt % of the total weight of the active material.
6. A method for producing the positive electrode active material according to claim 1, comprising the steps of: (a) coating a surface of a lithium transition metal oxide particle with an amorphous carbon-based material in the form of a coating; and (b) A method for producing a positive electrode active material, comprising the step of secondarily coating the surfaces of the primarily coated particles with carbon nanotubes to produce a positive electrode active material.
7. 7. The method of claim 6, wherein in step (a), the amorphous carbon-based material has a hollow structure, and the structure collapses during coating, thereby physically binding the amorphous carbon-based material to the surface of the lithium transition metal oxide in the form of a coating.
8. The method of claim 6, wherein the first coating in step (a) and the second coating in step (b) are performed by a mechanofusion method.
9. The method of claim 6 , wherein in step (b), the carbon nanotubes form π-π interactions with the amorphous carbon-based material.
10. 7. The method of claim 6, wherein the amorphous carbon-based material in step (a) and the carbon nanotubes in step (b) are each coated in an amount of 0.01 to 5 wt % of the total weight of the active material.
11. A positive electrode active material according to claim 1, comprising a binder, A free-standing film, wherein the binder comprises polytetrafluoroethylene (PTFE).
12. The freestanding film according to claim 11 , wherein the polytetrafluoroethylene is in the form of fibers surrounding the active material.
13. The freestanding film of claim 11 , wherein the freestanding film further comprises a conductive material.
14. The room temperature tensile strength of the free-standing film is 0.17 to 1 kgf / mm 2 12. The freestanding film of claim 11, wherein
15. A dry positive electrode, comprising the free-standing film according to claim 11 formed on a positive electrode current collector.
16. A secondary battery comprising the dry positive electrode according to claim 15.
Citation Information
Patent Citations
Conductive agent / positive electrode active material complex for lithium secondary battery, manufacturing method of conductive agent / positive electrode active material complex for lithium secondary batery, positive electrode for lithium secondary battery, and lithium secondary battery
JP2006128119A
Electrode material, electrode plate, secondary battery, and manufacturing method for the electrode material
JP2009043514A
Nonaqueous electrolyte battery
JP2017073334A
Compositions and methods for energy storage devices having improved performance
WO2019103874A1
